Flexão normal composta em seções retangulares de concreto armado em situação de incêndio - Marcelo Paixao Pinto Rodrigues (2009)
This work presents a general structural design method for reinforced concrete elements subjected to fire according to the Brazilian Standard ABNT NBR 15200:2004. The developed method evaluates reinforced concrete rectangular cross-sections subjected to compound flexure for different fire resistance required times specified by the BrazilianStandard ABNT NBR 14432:2000. The temperature distribution along the elements cross-section considering the non-linearity was obtained using the program THERSYS, a three-dimensional temperature distribution simulation system for buildings subjected to fires that uses the finite element method and which was developed at the Structural Engineering Department from the Federal University of Minas Gerais. An algorithm was implemented using the Visual Basic programminglanguage within the MS Excel spreadsheet environment to design rectangular reinforced concrete sections with symmetrical steel bar arrangement at normal temperatures (i.e., 20ºC). Electronic spreadsheets were developed to calculate and draw interactivediagrams of (axial force) x (bending moment) at 20ºC, for each fire resistance required time specified by the Brazilian standard (i.e., 30, 60, 90 e 120 minutes) and also for a structure which had been previously exposed to fire and cooled down back to 20ºC.